2009
DOI: 10.1103/physrevd.80.086009
|View full text |Cite
|
Sign up to set email alerts
|

Extremal correlators and Hurwitz numbers in symmetric product orbifolds

Abstract: We study correlation functions of single-cycle chiral operators in Sym N T 4 , the symmetric product orbifold of N supersymmetric four-tori. Correlators of twist operators are evaluated on covering surfaces, generally of different genera, where fields are single-valued. We compute some simple four-point functions and study how the sum over inequivalent branched covering maps splits under OPEs. We then discuss extremal n-point correlators, i.e. correlators of n−1 chiral and one anti-chiral operators. They obey … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(118 citation statements)
references
References 42 publications
7
111
0
Order By: Relevance
“…Applying symmetric orbifold techniques to a free field realisation, the chiral primary operators can be easily constructed [60,93] and their correlation functions explicitly computed [94][95][96][97][98]. Even though the free orbifold point may be a singular point in the moduli space of the D1-D5 CFT [99], it has been shown that the three-point correlation functions of chiral primaries computed at this point perfectly match those computed in the worldsheet WZW model CFT [100,101], as well as those computed in supergravity [56].…”
Section: A Few Facts About Chiral Primariesmentioning
confidence: 99%
“…Applying symmetric orbifold techniques to a free field realisation, the chiral primary operators can be easily constructed [60,93] and their correlation functions explicitly computed [94][95][96][97][98]. Even though the free orbifold point may be a singular point in the moduli space of the D1-D5 CFT [99], it has been shown that the three-point correlation functions of chiral primaries computed at this point perfectly match those computed in the worldsheet WZW model CFT [100,101], as well as those computed in supergravity [56].…”
Section: A Few Facts About Chiral Primariesmentioning
confidence: 99%
“…These changes move us to different points in the moduli space of the CFT. It has been conjectured that we can move to a point called the 'orbifold point' where the CFT is particularly simple [51][52][53][54][55][56][57][58][59][60]. At this orbifold point the CFT is a 1+1 dimensional sigma model.…”
Section: The Cftmentioning
confidence: 99%
“…These changes move us to different points in the moduli space of the CFT. It has been conjectured that we can move to a point called the 'orbifold point' where the CFT is particularly simple [59][60][61][62][63][64][65][66][67][68]. At this orbifold point the CFT is a 1+1 dimensional sigma model.…”
Section: The Cftmentioning
confidence: 99%